How Red Tides Impact Manatees - Brittany Hall-Scharf; Armando J. Ubeda (EDIS, 2019)
One of Florida's keystone species, manatees help to maintain healthy coastal and riverine ecosystems and are economically important for many coastal communities. Effective protection measures implemented in Florida for many years allowed state and federal regulators to reclassify manatees from Endangered to Threatened in 2017. Red tides, especially persistent blooms during winter months, can be one of the largest killers of Florida manatees, and they may become endangered again if they are subjected to increased mortality and stress. Understanding how red tides affect manatees and how can you help is critical. This 5-page fact sheet written by Brittany Hall-Scharf and Armando Ubeda and published by the UF/IFAS Florida Sea Grant College Program will explain what red tides are, how they harm manatees, and what you can do to help. http://edis.ifas.ufl.edu/sg188